Emergence of charge-transfer-to-solvent band in the absorption spectra of hydrogen halides on ice nanoparticles: spectroscopic evidence for acidic dissociation - Oncák, Milan; Slavícek, Petr; Poterya, Viktoriya; Fárník, Michal; Buck, Udo (The journal of physical chemistry. A, 2008)
Extensive ab initio calculations complemented by a photodissociation experiment at 193 nm elucidate the nature of hydrogen halide molecules bound on free ice nanoparticles. Electronic absorption spectra of small water clusters (up to 5 water molecules) and water clusters doped with hydrogen fluoride, hydrogen chloride and hydrogen bromide were calculated. The spectra were modeled at the time-dependent density functional (TDDFT) level of theory with the BHandHLYP functional using the reflection principle. We observe the emergence of a charge-transfer-to-solvent (CTTS) band in the absorption spectra upon the acidic dissociation of the hydrogen halides. The CTTS band provides a spectroscopically observable feature for the acidic dissociation. The calculated spectra were compared with our new experimental photodissociation data for larger water clusters doped with HCl and HBr. We conclude that HCl and HBr dissociate to a large extent on the surface of ice nanoparticles at temperatures near 120 K and photoactive products are formed. The acidic dissociation of HX leads to an enhancement by about 4 orders of magnitude of the HCl photolysis rate in the 200-300 nm region, which is potentially relevant for the halogen budget in the atmosphere.